On the Medical Works of Barhebraeus: With a Description of the Abridgement of Ḥunain’s Medical Questions - Takahashi, Hidemitsu (Aramaic studies, 2017)
While the Syriac polymath Gregory Barhebraeus (1225/6–86) is better known for his contributions in other fields, his original training was probably in medicine, and he is known to have written a number of works on the subject. No Syriac work on medicine by Barhebraeus is known to have survived, but four such works written in Arabic have, and references to matters related to medicine are also to be found in his works in other fields. In this article, we present a brief overview of what is known about the medical works of Barhebraeus, along with a somewhat more detailed description of one of the surviving works, namely his abridgement of Ḥunain’s Medical Questions.